One-Step Electrodeposition of MnO2-Graphitic Carbon Nitride Composite Layer on Screen Printed Electrode for Electrocatalytic Dopamine Sensing - Kumar Singh A.; Singh A.; Rosy (My University, 2025)
Electroanalysis using screen-printed electrodes offers a cost-effective, rapid, and on-site analyte quantification. Nevertheless, ensuring the necessary stability, sensitivity, and selectivity of SPE in order to perform precise ultra-low-level analyses is critical. The use of nano-structured materials for surface functionalization is one of the most prevalent strategy to augment the sensitivity and selectivity of sensors. However, the selection of the surface functionalization technique and material plays a crucial role. The present study outlines a single step electro-functionalization of the screen-printed sensor (SPE) with a carbon–metal oxide composite consisting of graphitic carbon nitride and manganese oxide (gCN.MnxOy). The electrodeposited gCN.MnO2 layer has been thoroughly analysed using spectroscopic, microscopic, and electrochemical techniques. As a test case, the electro-functionalized SPE was used to quantify dopamine by monitoring its electrocatalytic oxidation. Due to π-π interaction between the aromatic ring structures of the gCN and dopamine molecules, H-bonding, enhanced electroactive site, and facilitated charge transfer at the MnO2.gCN surface layer, the modified SPE exhibited a 15-fold higher peak current and a negative potential shift of 150 mV for DA oxidation. Being 44 times more sensitive, gCN.MnO2|SPE exhibited a detection limit of 10 nM compared to 5.36 µM for the unmodified electrode. As proof of application, the gCN.MnO2|SPE successfully estimated dopamine in pharmaceutical formulations, banana peel, and clinical samples namely saliva, urine and blood serum with an error of less than 9 %. We believe, the proposed modification protocol has the potential to create low-cost disposable functional interfaces that match the desirable properties of commercial products. © 2024 Elsevier B.V.